Psychosocial factors associated with physical activity level among undergraduate students in a public university in Malaysia - AL-Hassany, Noor Ahmed; Abu Saad, Hazizi; Abu Zaid, Zalina; Mohd Shukri, Nurul Husna (University of Shanghai for Science and Technology, 2020)
This cross-sectional study aimed to determine the association of psychosocial factors with physical activity levels among undergraduate students aged 18 to 30 years. A sample of 261 students from Universiti Putra Malaysia (n = 261; 138 males; 123 females) participated in the study. The respondents have been selected through a probability-based cluster sampling. A self-administered questionnaire was used to gather information regarding the socio-demographic characteristics(age, ethnicity, family household number, allowance income, and parent’s monthly income), psychosocial factors (self-efficacy, social support, and perceived benefit), and physical activity levels, which was accessed using Global Physical Activity Questionnaire (GPAQ). Multiple linear regression analysis was performed to determine factors associated with physical activity levels. The highest percentage of respondents (63.2%) were classified as having a moderate physical activity, followed by vigorous (24.9%)and low physical activity (11.9%). The findings of multiple linear regression revealed that self-efficacy (Beta = 0.137, p = 0.049) and physical performance (Beta = 0.193, p = 0.002) were significant predictors of physical activity levels. Therefore, enhancements in self-efficacy and positive perception toward having better physical performance could be used as a strategy to increase physical activity levels among students in the university.